Using the CS2013 Body of Knowledge to Reflect on our Security Courses (Journal of The Colloquium for Information Systems Security Education, 2013)
The ACM/IEEE Computing Curriculum 2013 is a community effort with representation from Academia and industry to outline curricular recommendations for undergraduate Computer Science degree programs. The effort began in 1968 [1] and conducts a complete review every ten years. The previous complete review was completed in 2001. [2] The current 2013 review is being developed to incorporate rapidly changing topics as technology and the world's use of technology evolves; however must do so within the curricular constraints of a complete undergraduate curriculum. This effort describes the architecture of CS2013 and the lessons learned in mapping our curriculum against the CS2013 computing curriculum.